1999
DOI: 10.1892/0891-6640(1999)013<0529:tppid>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Partial Pericardiectomy in 13 Dogs

Abstract: Thirteen dogs with cardiac tamponade resulting from pericardial effusion were prospectively evaluated to determine feasibility and outcome of thoracoscopic partial pericardiectomy. A lateral thoracoscopic approach allowed adequate exposure to remove a 4-to 5-cm-diameter section of pericardium in all dogs. Complete resolution of cardiac tamponade occurred in all dogs for which there was follow-up (11 dogs). Ten of 13 dogs (76.9%) had neoplastic pericardial effusion. One of these dogs remains alive at 220 days p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…There are also other studies describing different approaches and techniques for thoracoscopic pericardiectomy (Jackson et al 1999, Dupré et al 2001, Mayhew et al 2009). In these studies, lateral or paraxiphoid approaches with one-lung ventilation were used (Jackson et al 1999;Mayhew et al 2009). One-lung ventilation has been shown to detrimentally affect gas exchange and haemodynamic function at least experimentally (Kudnig et al 2003).…”
Section: Complicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…There are also other studies describing different approaches and techniques for thoracoscopic pericardiectomy (Jackson et al 1999, Dupré et al 2001, Mayhew et al 2009). In these studies, lateral or paraxiphoid approaches with one-lung ventilation were used (Jackson et al 1999;Mayhew et al 2009). One-lung ventilation has been shown to detrimentally affect gas exchange and haemodynamic function at least experimentally (Kudnig et al 2003).…”
Section: Complicationsmentioning
confidence: 99%
“…Apart from phrenic nerve and wound complications, lung laceration and intraoperative bleeding have been described with thoracoscopy (Jackson et al 1999). In a recent study, fatal hypotension was reported in 2 of 36 cases undergoing thoracoscopic pericardiectomy (Case et al 2013).…”
Section: Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3,6,7 With presumed idiopathic cases, a complete pericardioscopic evaluation is necessary to reduce the chance of a missed diagnosis and a larger pericardectomy is indicated. 2,8 Because masses are common on the right auricle and heart base ( Fig.…”
mentioning
confidence: 99%